Embodied Databases: Attending to Research ‘Places’ through Emotion and Movement - Kati Fargo Ahern (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
A simulation exercise helps students translate their kinesthetic and emotional responses to database research into heightened rhetorical awareness and knowledge of information technology.